Anti-dengue activity of super critical extract and isolated oleanolic acid of Leucas cephalotes using in vitro and in silico approach - Sulochana Kaushik; Lalit Dar; Samander Kaushik; Jaya Parkash Yadav (BMC, 2021)
Abstract Backgrounds Leucas cephalotes is a common ethnomedicinal plant widely used by traditional healers for the treatment of Malaria and other types of fever. Oleanolic acid and its derivatives have been reported for various types of pharmacological activities, such as anti-inflammatory, antioxidant, anticancer, hepatoprotective, anti-HIV and anti-HCV activity. Methods L.cephalotes plant extracts were prepared by supercritical fluid extraction (SFE) method and oleanolic acid was isolated by preparatory thin-layer chromatography. The compound was identified and characterize by using ultraviolet-visible spectroscopy (UV-VIS), Fourier transform infra-Red spectroscopy (FT-IR) and high-performance thin-layer chromatography (HPTLC). The structure of the compound was elucidated by proton nuclear magnetic resonance (1HNMR) and carbon nuclear magnetic resonance (1CNMR) and the purity checked by differential scanning calorimetry (DSC). The MTT assay was used to determine the toxicity of plant extract and oleanolic acid using a microplate reader at 595 nm. The anti-dengue activity of plant extract and oleanolic acid was tested in vitro and in silico using real-time RT-PCR. Results The optimum yield of the extract was obtained at 40 °C temperature and 15Mpa pressure. The maximum non-toxic dose (MNTD) of plant extract and oleanolic acid were found as 46.87 μg/ml and 93.75 μg/ml, respectively in C6/36 cell lines. UV spectrophotometer curve of the isolated compound was overlapped with standard oleanolic acid at 232 nm. Superimposed FT-IR structure of the isolated compound was indicated the same spectra at 3433, 2939, 2871, 1690, 1500,1463, 1387, 1250, 1209, 1137 and 656 position as per marker compound. HPTLC analysis showed the retention factor of L. cephalotes extract was 0.19 + 0.06 as similar to the standard oleanolic acid chromatogram. The NMR structure of the isolated compound was identified as similar to the marker oleanolic acid structure. DSC analysis revealed the purity of isolated oleanolic acid was 98.27% with a melting point of 311.16 °C. Real-time RT PCR results revealed that L. cephalotes supercritical extract and isolated oleanolic acid showed 100 and 99.17% inhibition against the dengue − 2 virus when treated with MNTD value of plant extract (46.87 μg/ml) and the test compound (93.75 μg/ml), respectively. The molecular study demonstrated the binding energy of oleanolic acid with NS1and NS5 (non-structural protein) were − 9.42 & -8.32Kcal/mol, respectively. Conclusions The SFE extract L. cephalotes and its active compound, oleanolic acid inhibiting the activity of dengue-2 serotype in the in vitro and in silico assays. Thus, the L.cephalotes plant could be an excellent source for drug design for the treatment of dengue infection.